Incorporation of molecular hydrogen into solvents increases the extraction efficiency of phenolics, flavonoids, anthocyanins, and antioxidants: the case of lemon peels - Alwazeer, Duried; Elnasanelkasim, Muhammed Allam; Çiğdem, Ayhan; Engin, Tunahan; LeBaron, Tyler W. (Frontiers in Sustainable Food Systems, 2023)
The impact of hydrogen infusion into solvents on the extraction of phytochemicals was evaluated. Pure (water, ethanol, methanol) and hydrogen-rich solvents at temperatures (25°C and 35°C) were used for extracting phenolics, flavonoids, anthocyanins, and antioxidants from lemon peel. Incorporating hydrogen into all solvents increased the extraction of all phytochemicals. The hydrogen incorporation into solvents led to the highest increase in phenolics and flavonoid contents shown for hydrogen-rich methanol (HRM) followed by hydrogen-rich ethanol (HRE) at both 25°C and 35°C. The highest antioxidant extraction was shown for HRM. The hydrogen incorporation showed the highest phytochemical extraction in methanol and at 35°C. The increase in temperature increased the extraction efficiency, but less efficiently than the hydrogen incorporation. The HPLC phenolic profile confirmed the positive effect of both temperature and hydrogen incorporation on the extraction of flavonoids and non-flavonoids. The improvement of the phytochemical extraction by the proposed method can bring many economic and ecological advantages.